Effective inactivation of Nipah virus in serum samples for safe processing in low-containment laboratories - Watanabe, Shumpei; Fukushi, Shuetsu; Harada, Toshihiko; Shimojima, Masayuki; Yoshikawa, Tomoki; Kurosu, Takeshi; Kaku, Yoshihiro; Morikawa, Shigeru; Saijo, Masayuki (Virology journal, 2020)
Nipah virus (NiV) is an emerging zoonotic paramyxovirus that causes severe encephalitis and respiratory disease with a high mortality rate in humans. During large outbreaks of the viral disease, serological testing of serum samples could be a useful diagnostic tool, which could provide information on not only the diagnosis of NiV disease but also the history of an individual with previous exposure to the virus, thereby supporting disease control. Therefore, an efficient method for the inactivation of NiV in serum samples is required for serological diagnosis. We determined the optimal conditions for the inactivation of NiV infectivity in human serum using heating and UV treatment. The inactivation method comprised UV irradiation with a cover of aluminum foil for 30 min and heating at 56 °C for 30 min. With an optimized protocol for virus inactivation, NiV infectivity in serum samples (containing 6.0 × 10 TCID ) was completely inactivated. We developed a recommended protocol for the effective inactivation of NiV. This protocol would enable a regional or local laboratory to safely transport or process samples, including NiV, for serological testing in its biosafety level-2 facility.